Characteristics of mentoring programmes in the early phase of medical training at the Universiti Sains, Malaysia - Mat Nor, Zarawi M.; M. Yusoff, Saiful Bahri; Abdul Rahim, Fuad A. (Taibah University, Madinah, Kingdom of Saudi Arabia, 2017)
Objective: Mentoring programmes are important elements of the personal and professional development of medical students. Mentors must focus on the real issues that students face during the mentoring process. This study explores the need for mentoring programmes for first-year medical students at the Universiti Sains, Malaysia (USM). Methods: A qualitative case study was conducted with medical students who were in the early phases of their training. Purposive sampling was employed to select the study participants. Data collection was carried out using semi-structured interviews. The interviews were recorded and transcribed verbatim, and they were later analysed using NVivo 10 software and employing open coding, axial coding and selective coding techniques. Nine medical students participated in the study. To ensure trustworthiness of the data, member checks, an audit trail, the Cohen kappa index, and peer checking were utilized. Results: Based on thematic analysis, four themes and seven categories were identified. Themes include soft skills, an academic overview, social skills and motivation from mentors. Categories include time management, study skills, communication skills, social adjustment, social activities, moral support and personal support. Conclusion: Results indicate that mentoring is essential to medical students in developing their identity and professional maturity. The effectiveness of the mentoring programme is supported by several factors that, as a whole, lead to the development of a professional graduate.